PENGARUH PEMBERIAN SUSU FERMENTASI SINBIOTIK (Lactobacillus plantarum Dad-13-Fruktooligosakarida) DENGAN FORTIFIKASI GANDA Fe DAN Zn TERHADAP PERTUMBUHAN TIKUS - , MOH. DARUS SALAM, Siti Helmyati, DCN., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Fortification is one solution to solve nutrition and health problem in community. Micromineral deficiensies during growth period are highly prevalent in Indonesia. Deficiensies of iron and zinc during growth period are correlated with growth failure. Sinbiotic fermented milk is one of the potential food carrier for iron and zinc fortification. Probiotic in sinbiotic fermented milk can enhance absorption of mineral then micromineral need in the body will be fullfilled Objective : To investigate the effects of sinbiotic fermented milk (Lactobacillus plantarum Dad-13-fructooligosaccharide) with double fortified Fe and Zn on the growth of rat. Method : Experimental study with randomized control trial was used in this study. Fifteen Wistar rats age 84 days are divided into 3 groups. The NZ group was given sinbiotic fermented milk with fortifican NaFeEDTA-Zn Acetate, the TZ group was given sinbiotic fermented milk with fortifican Fe Gluconate-Zn Acetate, while the TF group was given only sinbiotic fermented milk without fortified with the ratio between Fe and Zn is 100 ppm : 50 ppm. Milk is distributed daily during 2 months. The measurement of tail length was taken once time per week, while the measurement of humerus and femur length was taken at the end of experiment. Result : After 2 months treatment, a significant difference was found in the bone length (p = 0.025) at the humerus bone on NZ and TF group , but it was not found in the tail length on each week (p > 0.05). Conclusion : Distributed of sinbiotic fermented milk (Lactobacillus plantarum dad-13-fructooligosaccharide) with double fortified Fe and Zn and sinbiotic fermented milk without fortified has same effects on the growth of rat.